Encyclopedia of Internet technologies and applications - Freire, Mario Marques 1969-; Periera, Manuela (Gale virtual reference library, 2008)
Provides the most thorough examination of Internet technologies and applications for researchers in a variety of related fields. For the average Internet consumer, as well as for experts in the field of networking and Internet technologies.